Pengembangan Media Pembelajaran Berbasis Aplikasi Adobe Flash Pada Materi Kalor, Perpindahan Kalor Serta Teori Kinetik Gas untuk Meningkatkan Pemahaman Konsep Siswa - Wahyudi, Wahyudi; Aswirna, Prima; Hurriyah, Hurriyah; Amalina, Amalina (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2020)
The purpose of this study is to produce learning media based on Adobe Flash applications that are valid, practical and effective. This type of research is development research using the ADDIE model. The results of this study are adobe flash based learning media which are very valid with an average of 84.05%, very practical with an average of 76.5%, very effective with an average of 74% and an understanding of concepts with a value of 74.2. Based on the results of the study, it can be concluded that the learning media based on Adobe Flash application to improve students' understanding of concepts is very valid, very practical, and very effective in supporting the understanding of concepts in heat material, heat transfer and kinetic gas theory.